Acid Washing of MnOx‐SBA‐15 Composites as an Efficient Way to Improve Catalytic Properties in HCHO Total Oxidation. Issue 8 (25th May 2020) - Rochard, Guillaume; Royer, Sébastien; Giraudon, Jean‐Marc; Lamonier, Jean‐François
Abstract: The effect of 10 M HNO3 treatment on MnOx nanoparticles mostly confined inside the porous channels of SBA‐15 with low Mn average oxidation state (Mn AOS<3) has been investigated with regard to the physico‐chemical properties of the catalysts as a function of Mn loading (10, 20, 30 wt%) to be tested in the total oxidation of formaldehyde. The acid‐treated catalysts were extensively characterized (ICP, N2 ‐sorptions, H2 ‐TPR, TGA/DSC, HRTEM and XPS). It is found that the acid treatment promotes the redox and textural properties of the catalyts. Such property improvements allow to get more efficient catalysts in total oxidation of HCHO. Indeed, the standardized rate rs expressed as mmoles of formaldehyde converted into CO2 per mole of Mn per hour at 130 °C increases by 5 and by 4 for the 20 wt% Mn and 30 wt% Mn‐based catalysts, respectively. Abstract : Washed away : Acid washing of MnOx‐SBA‐15 composites is reported as an efficient way to improve the catalytic properties with regard to HCHO total oxidation.